The competence of village clinicians in the diagnosis and management of childhood epilepsy in Southwestern China and its determinants: A cross-sectional study - Hongmei Yi; Huidi Liu; Zhiping Wang; Hao Xue; Sean Sylvia; Haonan Shi; Dirk E. Teuwen; Ying Han; Jiong Qin (Elsevier, 2020)
Background: Due to lack of neurologists in low- and middle-income countries, communities of patients living with epilepsy are calling for task-shifting of diagnosis and management from physicians to paramedical providers in the primary health care systems to narrow the huge treatment gap. Evidence to guide this work has been limited. This study assesses the competence of village clinicians (VC)- mostly paramedical providers- in the diagnosis and management of a presumptive case of childhood epilepsy and its determinants. Methods: A cross-sectional study was conducted in rural areas of a province in Southwestern China from July 2017 to January 2018. We randomly selected 370 VCs who practiced Western medicine and assumed the main responsibility of providing medical services in his/her clinic. A standardized clinical vignette based on national clinical practice guidelines was used to evaluate clinicians' competence in three domains: number and proportion of recommended (and essential) checklist (questions, examinations, and tests) completed, correctness of diagnosis, and correctness of case management. Findings: Though VCs completed 14•3% (IQR 9•5%-19•1%) of the recommended checklist, 63•2% (234/370, 95%CI 58•2%-68•0%) provided a correct diagnosis. Only 1•6% of VCs (6/370, 95%CI 0•7%-3•5%) gave correct management with both correct medication and referral, however 90•3% (334/370, 95%CI 86•8%-92•9%) provided partially correct management by referring patients to upper-level health facilities (89•5%, 331/370, 95%CI 85•9%-92•2%) or prescribing anti-epileptic drugs (AEDs) correctly (0•8%, 3/370, 95%CI 0•3%-2•4%). Around 1/4 VCs referred patients to Township Health Centers which usually were not staffed with pediatric neurologists. Fewer provided helpful medical advice to patients for daily management. The heuristic process was found to be negatively associated with the proportion of the recommended checklist that VCs completed, which is positively associated with correctness of diagnosis. Interpretation: Most VCs could diagnose and refer childhood epilepsy patients correctly; however, they lacked competence when it came to assuming the responsibility of primary care providers, referring efficiently, refilling AEDs, as well as supervising and instructing daily management of patients. Funding: HY received the funding for this study from the "Health and Hope Fund" of the Business Development Center of the RCSC (Beijing) and UCB (Belgium). UCB provided support in the form of a salary for author DET.